2017
DOI: 10.1016/j.mrgentox.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Advanced Glycation End-Products (AGEs) by glycoxidation mediated by copper and ROS in a human serum albumin (HSA) model peptide: reaction mechanism and damage in motor neuron cells

Abstract: Glucose, in the presence of reactive oxygen species (ROS), acts as an as an oxidative agent and drives deleterious processes in Diabetes Mellitus. We have studied the mechanism and the toxicological effects of glucose-dependent glycoxidation reactions driven by copper and ROS, using a model peptide based on the exposed sequence of Human Serum Albumin (HSA) and containing a lysine residue susceptible to copper complexation. The main products of these reactions are Advanced Glycation End-products (AGEs). Carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 87 publications
3
12
0
Order By: Relevance
“…Recent studies have shown that glucose oxidation by a hydroxyl radical leads to the formation of a-oxoaldehyde as 3-deoxyglucosone [39], that agrees with the proposed mechanism of non-enzymatic synthesis of methylglyoxal. The data obtained in our study also highlight the important role the free radical reactions play in non-enzymatic transformations of sugars and other carbonyl compounds.…”
Section: Formation Of Superoxide and Organic Free Radicals In The Reasupporting
confidence: 81%
“…Recent studies have shown that glucose oxidation by a hydroxyl radical leads to the formation of a-oxoaldehyde as 3-deoxyglucosone [39], that agrees with the proposed mechanism of non-enzymatic synthesis of methylglyoxal. The data obtained in our study also highlight the important role the free radical reactions play in non-enzymatic transformations of sugars and other carbonyl compounds.…”
Section: Formation Of Superoxide and Organic Free Radicals In The Reasupporting
confidence: 81%
“…AGEs can also act by bonding to RAGEs (receptor for advanced glycation end-products) in plasma membrane and this interaction triggers different signaling pathways involved in apoptosis, inflammation, angiogenesis, and vasopermeability [102]. Furthermore, AGEs increase the production of reactive oxygen species (ROS), which impact genome integrity [103,104]. The increase in ROS production can, in turn, promote the production of more AGEs, thereby forming a vicious circle [101].…”
Section: Vitamin B6 and Diabetes Complicationsmentioning
confidence: 99%
“…Finally, the glycation system also induced the accretion of AGEs ( Figure 6 ) and other fluorescent and colored pigments in HSA, spectrophotometrically measured as yellowness ( Figure 7 ). AGEs are recognized as a remarkable expression of glycosative stress on plasma proteins [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite being a heterogeneous group of macromolecules generated at advanced stages of the Maillard reaction, their biological effects are remarkable. They have been found to induce cellular toxicity and contribute to complications in diabetic patients [ 37 ]. Their formation under physiological conditions takes several months of sustained exposure to circulating glucose while it is accelerated in hyperglycemia conditions [ 38 ].…”
Section: Resultsmentioning
confidence: 99%